EVALUATION OF FACTORS INFLUENCED BY THE DIGITAL-ELECTRONIC COMMERCE SYSTEM IN REDUCING ECONOMIC EXPECTATIONS - Ravshanova Muhayyo Makhmanazarovna (Bright Mind Publishing, 2025)
In this article, the author analyzes the role of digital-e-commerce in the development of the economy and its main structural aspects, emphasizing that digital-e-commerce serves to increase economic efficiency through the automation of business processes, the introduction of digital technologies and the use of innovative solutions. The impact of factors such as Internet technologies, electronic payment systems, marketing strategies, logistics services and the legislative system on e-commerce is also considered. The article also analyzes the role of e-commerce in the modern economy and its future prospects.
Keywords: Digital, electronic commerce, model, online platforms, innovative economy, resulting and influencing factors, internet, online sales, electronic payment systems, logistics services, marketing strategies.